(untitled) (Journal of Asian Development Studies, 2025)
This paper explores George Bernard Shaw’s use of the “life force theory" in his seminal play Man and Superman. As a vital philosophical concept, life force is based on the belief in creative evolution. This doctrine becomes a drive to continuously perfect itself by creating better forms. The characters and themes of the novel are looked at in relation to one theory of how this occurs, in particular, the embodiment of the unconscious life force, Ann, and her relentless pursuit of Tanner, corresponding to the embodiment of the conscious life force. The analysis sets Man and Superman within the intellectual streams of its time while concurrently exploring Shaw’s embrace of Nietzsche, Schopenhauer, and Lamarck’s ideas. This study combines qualitative methods to spotlight the play’s philosophical, comedic, and dramatic levels and advance the idea that Shaw utilizes the exchange of conscious and unconscious forces to espouse an evolutionary progression and social change.